THE IMPLEMENTATION OF THE NEURAL NETWORK FOR THE CLASSIFICATION PROBLEM - Lisovik, Ulyana; Lipchanskiy, Oleksandr (International Journal of Computing, 2014)
The example of NN realization is considered. Also description of all its design stages from NN function model description to its timing and hardware characteristics estimation is considered. NN structural model is presented in VHDL code. Through SynplifyPro 7.0 package from Synplicity® the system synthesis with the orientation on Virtex- II XC2V6000 family is made out. The estimation of the optimality of the synthesized NN model utilization is accomplished. NN structures are shown; hardware costs are taken to the table.